2021
DOI: 10.1007/s12564-021-09711-y
|View full text |Cite
|
Sign up to set email alerts
|

What should be done to develop ICT-based PE class in the era of the Fourth Industrial Revolution?: using AHP and IPA analysis within the Korean educational contexts

Abstract: This study aims to explore educational and political efforts for PE teachers to implement ICT-based PE class by analyzing three significant phases (PE teacher, the curriculum, and teaching environment). To reach the goal of this study, we conducted AHP and IPA analysis to find out the priorities in order to implement ICT-based PE class. As a result, a total of 27 detailed contents were created by IPA analysis. Based on the IPA results, we interrogated what detailed contents should be firstly applied into actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For this reason, teachers are required to develop managerial skills. Joo and Choi (2021) found that even if technological devices and instruments are readily available, they will be useless if educators lack the basic skills and knowledge necessary for integrating them into their classroom practices. Bowman et al (2022) argued that the quality and quantity of professional development programs for teachers impact instructors' level of knowledge in working with ICT.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, teachers are required to develop managerial skills. Joo and Choi (2021) found that even if technological devices and instruments are readily available, they will be useless if educators lack the basic skills and knowledge necessary for integrating them into their classroom practices. Bowman et al (2022) argued that the quality and quantity of professional development programs for teachers impact instructors' level of knowledge in working with ICT.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bowman et al (2022) argued that the quality and quantity of professional development programs for teachers impact instructors' level of knowledge in working with ICT. Joo and Choi (2021) added that effective training on pedagogical content is also needed rather than solely focusing on training teachers regarding how to utilize ICT. Bowman et al (2022) stated that such professional development content must address teachers' needs for their classes before committing any changes to their skills and knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The IPA matrix in Figure 1 consists of four quadrants, with the x-axis representing the performance attribute and the y-axis representing the importance attribute. Specifically, these include: "keep up the good work" (QI: A state in which learners recognize an attribute as important and high performing), "concentrate here" (QII: A state in which an attribute's importance is recognized, but the level of execution is not good), "possible overkill" (QIII: A state in which the attribute is unimportant and poorly executed), and "low priority" (QIV: A state in which the attribute is not important, but well executed) [31].…”
Section: Ipamentioning
confidence: 99%
“…Thus, academic studies cease to be an autonomous field and turn into a structure shaped by external demands (Dearlove, 1997). Joo and Choi (2021) focus on the importance of improving skills and professionalism in an educational ecosystem and increasing the autonomy. Critics argue that all of these factors cause professional erosion and decreasing skills for lecturers (Runte ve Runté, 2007).…”
Section: Transformation In Lecturers' Work and Skillsmentioning
confidence: 99%